2015
DOI: 10.1007/s10948-015-3132-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zinc Doping on the Structural and Magnetic Properties of Ni-Ga-Sm Polycrystalline Ferrites

Abstract: Polycrystalline Ni 1−x Zn x Fe 1.49 Ga 0.5 Sm 0.01 O 4 (0 ≤ x ≤ 0.5) spinel ferrite powders were prepared using standard ceramic method. Structural and magnetic properties of the sintered samples were investigated using X-ray powder diffraction, Mössbauer effect spectroscopy, and vibrating sample magnetometer. X-ray analysis confirmed the formation of single phase cubic spinel ferrites for all samples. The cation distribution obtained from the Mössbauer effect measurements suggested that Sm 3+ ions substituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…2 and Table 1. The lattice parameter (a) values are very close to the values observed for the bulk samples [3]. From Table 1, a initially increases up to x = 0.3 and then decreases for higher Zn content.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…2 and Table 1. The lattice parameter (a) values are very close to the values observed for the bulk samples [3]. From Table 1, a initially increases up to x = 0.3 and then decreases for higher Zn content.…”
Section: Introductionsupporting
confidence: 78%
“…For x ≥ 0.3, Zn 2+ ions unusually distributed in both A to B sites. Recently, the standard ceramic method was used to prepare Ga-, Zn-, and Sm-doped Ni 1−x Zn x Fe 1.49 Ga 0.5 Sm 0.01 O 4 (0.0 ≤ x ≤ 0.5) samples [3]. Our measurements confirmed that Sm 3+ ions favor the B sites and support magnetism in the studied system.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations